Distribution of antibiotic resistance genes in marine water and sediments in aquaculture areas in Khanh Hoa, Vietnam - Do, Uyen Thu; Tran, Son Hoang; Vu, Quang Dinh; Nguyen, Quang Huy (Vietnam Journal of Biotechnology, 2025)
The emergence of antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs) poses significant risks to ecological security and human health. Coastal areas affected by urban and aquaculture activities serve as critical reservoirs for pollutants, including ARGs. However, the data on the abundance and distribution of ARGs in marine sediments impacted by aquaculture activities in the East Sea, Vietnam, remain limited. This study investigated the distribution of ARGs across four aquaculture areas in the East Sea of Khanh Hoa province, Vietnam. The results revealed that sulfonamide-resistant genes, sul1 and sul2, were present at all sampling sites (100%), with abundance ranging from 2.4 × 102 to 2.0 × 105 copies/ml in seawater and from 2.0 × 105 to 2.57 × 107 copies/g in sediments. Tetracycline-resistant genes, including tetQ, tetM, and tetX, were detected at most sampling sites, with abundances ranging from 1.29 × 101 to 6.16 × 106 copies/ml in seawater and from 1.64 × 104 to 1.04 × 108 copies/g in sediments. The vancomycin-resistant gene (vanA) exhibited significant abundance, ranging from 1.38 × 103 to 3.22 × 104 copies/ml in seawater and from 1.14 × 106 to 1.9 × 107 copies/g in sediments. Finally, integron class 1 (intI1) was detected at all sampling sites (100%) in both seawater and sediments, with abundances up to 6.86 × 105 copies/ml in seawater and 2.06 × 108 copies/g in sediments. Given aquaculture's significant role in Vietnam's economic growth, implementing effective technologies and national policies to manage and mitigate antimicrobial resistance in aquaculture environments is crucial.